IJCM_338A: Burden Of Common Mental Health Disorders Using GHQ-12 Scale Among The Tribal And Rural Elderly Population In Mysore District. - Jolly Sebin; Khan Mudassir Azeez (Wolters Kluwer Medknow Publications, 2024)
Background: Common mental disorders (CMD) are a group of distress states manifesting with anxiety, depressive, and unexplained somatic symptoms and are the contemporary equivalent to the older concept of neurotic disorders. Various prevalence studies have shown that elderly population are more vulnerable to such mental health disorders as compared to the younger population. The available literature indicates that there is hardly any effort to understand the morbidity and the needs of such elderly people. Objective: i. To estimate the burden of common mental disorders among tribal and rural elderly population using GHQ -12. ii. To estimate the association between common mental disorders and sociodemographic factors. Methodology: This is a community based cross sectional study. It was among the tribal and rural elderly population of Mysore district from June to September 2023 using General Health Questionnairre-12(GHQ-12). The 12-Item General Health Questionnaire (GHQ-12) is the most extensively used screening instrument for common mental disorders. The GHQ-12 has generally demonstrated good sensitivity and specificity in various populations. The sampling method adopted for this study was multistage sampling and in the final stage participants were selected using simple random sampling Results: The prevalence of common mental disorders was 35% among rural elderly population and 43% among tribal elderly population. The prevalence of common mental disorders was found to be high among women in both rural and tribal elderly population and the difference was found to be statistically significant Conclusion: There are limitations in the study as cross-sectional type of study design was used. Further, analytical studies can be conducted to prove the causative association between common mental disorders and various socio- cultural factor. However, the findings of the study can be used to plan the necessary interventions in the field of elderly mental health